2013
DOI: 10.1007/s00266-012-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Transplantation: Volumetric Tools for Estimation of Volume Survival. A Systematic Review

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 67 publications
0
47
0
6
Order By: Relevance
“…Quantitative information about the rate of fat survival is important for guiding surgeons and patients. A recent review analysed several methods for evaluating this including 3D-SI [83]. The authors concluded that 3D-SI is a suitable tool when frequent follow-up and fast data acquisition is needed.…”
Section: Objective Assessment Of Outcomementioning
confidence: 96%
“…Quantitative information about the rate of fat survival is important for guiding surgeons and patients. A recent review analysed several methods for evaluating this including 3D-SI [83]. The authors concluded that 3D-SI is a suitable tool when frequent follow-up and fast data acquisition is needed.…”
Section: Objective Assessment Of Outcomementioning
confidence: 96%
“…According to a systematic review comparing different volumetric tools to estimate fat survival after fat grafting, magnetic resonance imaging and three-dimensional scanning provide highly accurate and highly reproducible results. 42 Magnetic resonance imaging offers all the necessary information: evaluation of fat survival and possible complications following fat grafting. However, frequent imaging may bother patients and is not cost effective.…”
Section: Limitationsmentioning
confidence: 99%
“…Fat grafting, commonly performed for reconstruction of soft tissue defects, is complicated by resorption rates ranging from 10% to 90% that often necessitate reoperation. [24][25][26] Initially described by Matsumoto et al in 2006, the addition of supplemental SVF cells/ASCs has been shown to improve fat graft retention. 27 However, several unknowns, including the optimum ratio of cells to lipoaspirate for the graft volume desired, remain to be determined before cell-assisted lipotransfer can be consistently used clinically.…”
Section: Discussionmentioning
confidence: 99%